UNHEARD VOICES: THE LOCATION OF WOMEN AS OTHERNESS IN JEAN RHYS’S WIDE SARGASSO SEA - Mohammed, Saz Hersh; Abdul, Zanyar Kareem (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
Jean Rhys’s Wide Sargasso Sea (1966) is a postcolonial story in which Antoinette, the Creole lady, is portrayed as the crazy woman in the attic. Thus, it is possible to see why Antoinette as a protagonist misses her identity and how madness works in a colonial and patriarchal culture by examining the connections between race and gender in Rhys' novel in light of Ania Loomba's ideas about colonialism and postcolonialism and linking it to psychoanalytic feminism with Julia Kristeva's notion of the abject. Race and gender are employed as metaphors for one another and to dehumanize the other among us, driving it insane. Postcolonial critics have debated Antoinette's otherness as a result of colonial rule; whereas, feminist theorists have frequently emphasized the patriarchal aspect of society and the connection between madness and the mother-daughter relationships of the novel. This study focuses on otherness and lunacy, which contains not only colonizer-colonized, male-female, and mother-daughter connections but also self-repression in a patriarchal and colonial culture, leading to Antoinette’s alienation and loss of identity. Overall, black women as being enslaved are picturized as ugly, something without an owner.